2004
DOI: 10.4049/jimmunol.173.2.1321
|View full text |Cite
|
Sign up to set email alerts
|

E-Prostanoid-3 Receptors Mediate the Proinflammatory Actions of Prostaglandin E2 in Acute Cutaneous Inflammation

Abstract: PGs are derived from arachidonic acid by PG-endoperoxide synthase (PTGS)-1 and PTGS2. Although enhanced levels of PGs are present during acute and chronic inflammation, a functional role for prostanoids in inflammation has not been clearly defined. Using a series of genetically engineered mice, we find that PTGS1 has the capacity to induce acute inflammation, but PTGS2 has negligible effects on the initiation of this response. Furthermore, we show that the contribution of PTGS1 is mediated by PGE2 acting throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…This conclusion derives from the results indicating that edema formation induced by PGE 2 injection is markedly prevented by the selective EP 3 L826266, but not the EP 2 AH6809 or EP 4 L161982 receptor antagonists. In fact, it has been recently demonstrated that edema formation and plasmatic extravasation induced by the topical application of arachidonic acid is found significantly decreased in mice with genic deletion of EP 3 receptors, whereas these responses remain unaffected in knockout mice for EP 1 , EP 2 , or EP 4 receptors (Goulet et al, 2004) In addition, Yuhki et al (2004) showed that IP, EP 2 , and EP 3 , but not EP 1 or EP 4 , receptor subtypes are largely implicated in exudate formation in the model of pleurisy induced by carrageenan in the mouse. Notably, we have also observed that the EP 3 receptor antagonist L826266 consistently inhibits carrageenan-induced edema in mice, to the same extent that it is able to reduce PGE 2 -mediated edema formation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion derives from the results indicating that edema formation induced by PGE 2 injection is markedly prevented by the selective EP 3 L826266, but not the EP 2 AH6809 or EP 4 L161982 receptor antagonists. In fact, it has been recently demonstrated that edema formation and plasmatic extravasation induced by the topical application of arachidonic acid is found significantly decreased in mice with genic deletion of EP 3 receptors, whereas these responses remain unaffected in knockout mice for EP 1 , EP 2 , or EP 4 receptors (Goulet et al, 2004) In addition, Yuhki et al (2004) showed that IP, EP 2 , and EP 3 , but not EP 1 or EP 4 , receptor subtypes are largely implicated in exudate formation in the model of pleurisy induced by carrageenan in the mouse. Notably, we have also observed that the EP 3 receptor antagonist L826266 consistently inhibits carrageenan-induced edema in mice, to the same extent that it is able to reduce PGE 2 -mediated edema formation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…by inflammatory mediators such as prostanoids (Goulet et al, 2004). Prostanoids consisting of the prostaglandins and thromboxanes are rapidly synthesized via the cyclooxygenase pathway in a variety of cells in response to various stimuli such as inflammation (Funk, 2001; for review, see Bos et al, 2004;Hata and Breyer, 2004).…”
Section: N-[(4r)-4-hydroxy-1-(1-methyl-1h-indol-3-yl)carbonyl-l-prolymentioning
confidence: 99%
“…EP1 is coupled to intracellular Ca 2+ mobilization via G q , EP2 and EP4 are coupled to stimulation of adenylyl cyclase via G s , and EP3 is mainly coupled to inhibition of adenylyl cyclase via G i . Among the four PGE receptors, the EP3 receptor was proposed to participate in arachidonic acid (AA)-induced edema formation (10). These results suggest that PGE 2 may function as a link to an increase in vascular permeability and edema formation (11).…”
mentioning
confidence: 87%
“…Functionally, PGE 2 interacts with the four receptor subtypes (EP1-4). EP1 and EP3 primarily contribute to inflammatory responses, whereas EP4 promotes both cell survival and growth by activating antiapoptotic and proliferative cellular signaling pathways (Fujino et al, 2003;Hase et al, 2003;Hoshino et al, 2003;Goulet et al, 2004;Joseph et al, 2005). Moreover, EP4 is constitutively expressed in the colonic epithelium and further induced during IBD, along with PGE 2 (WiercinskaDrapalo et al, 1999;Northey et al, 2000;Takafuji et al, 2000;Nitta et al, 2002).…”
mentioning
confidence: 99%